Validation of the REDS score in hospitalised patients who deteriorated and were admitted to the intensive care unit—a retrospective cohort study - Narani Sivayoham; Oliver Mason; Harriet O’Mara; Natasha Trenchard Turner; Katie Sysum; Georgina Wicks (BMJ Open Quality)
Background Hospitalised patients are at risk of deterioration and death. Delayed identification and transfer to the intensive care unit (ICU) are known to be associated with increased mortality rates. The Risk-stratification of Emergency Department suspected Sepsis (REDS) score was derived and validated in emergency department patients with suspected sepsis. It is unknown if the REDS score would risk-stratify undifferentiated hospitalised patients who deteriorate.Objectives To validate the REDS score in hospitalised patients who deteriorate.Methods This retrospective cohort single-centre study involved hospitalised adult patients who deteriorated and were transferred to the ICU between 1 April 2022 and 31 March 2023. The first admission to the ICU was studied. The National Early Warning Score2 (NEWS2), REDS, Sequential Organ Failure Assessment (SOFA) and change-in-SOFA (ΔSOFA) scores were calculated at the time of referral to the Critical Care Outreach Team (CCOT). The primary outcome measure was in-hospital all-cause mortality. The area under the receiver operator characteristic (AUROC) curves for the scores were compared. Test characteristics at the cut-off points individually and in combination were noted.Results Of the 289 patients studied, 91 died. The REDS score had the largest AUROC curve at 0.70 (95% CI 0.65 to 0.75), greater than the NEWS2 score at 0.62 (95% CI 0.56 to 0.68), p=0.03, and similar to the SOFA score 0.67 (95% CI 0.61 to 0.72), p=0.3. The cut-off points for the NEWS2, REDS, SOFA and ΔSOFA scores were >9, >3, >6 and >4, respectively. The sensitivity and specificity for a ΔSOFA≥2 was 91.2% (95% CI 83.4 to 96.1) and 15.7% (95% CI 10.9 to 21.5), respectively. REDS≥4 or NEWS2≥7 had a sensitivity of 87.9% (95% CI 79.4 to 93.8) and specificity of 29.3% (95% CI 23.1 to 36.2).Conclusion The prognostic performance of the REDS score was similar to the SOFA score, but greater than the NEWS2 score. The REDS score could be used in addition to the established NEWS2 score to risk-stratify hospitalised patients for mortality.